Provenienzforschung und Kunsthandel - Wehrle, Peter; Wehrle, Peter (Ernest Rathenau Verlag, 2023)
Mit Beiträgen von: Sabine Disterheft, Carolin Faude-Nagel, Christina Feilchenfeldt, Christian Fuhrmeister, Robert und Gudrun Ketterer, Stephan Klingen, Sarah von der Lieth, Mario-Andreas von Lüttichau, Susanne Meyer-Abich, Stefan Pucks, Anna B. Rubin, Theresa Sepp, Sandra Sykora, Agnes Thum, Katharina Thurmair und Peter Wehrle